Clan Culture dalam Organisasi: Studi Fenomenologi di Organisasi Jasa Ketenagalistrikan di Jawa Tengah - Setyowati, Ani; Permanasari, Rusdiana (Universitas Muhammadiyah Surakarta, 2024)
Organizational success cannot be separated from the work culture that develops in the organization. Clan culture is a culture that thrives in a work environment with a communicative and collaborative emphasis. Clan culture prioritizes deliberation for consensus because it prioritizes communication with family closeness or people who are closer. However, not all Clan cultures can be applied in all organizations such as in companies that are on an international scale. Because international-level companies prioritize the nature of professionalism and expertise in their field. The focus of the research was carried out in organizations engaged in electricity services in Central Java. The research method uses the phenomenological method. To obtain research results, researchers dig up information through interviews and observations at research locations. The interviews were conducted using a semi-structured method and succeeded in interviewing a number of 8 informants in several regional offices in Central Java. The results of the study show that the organizational character of the Clan culture approach reflects organizational members who are innovative, collaborative, and close in terms of communication so as to be able to support the creation of organizational goals.